Use of Natural Products in Leishmaniasis Chemotherapy: An Overview - Gervazoni, Luiza F. O.; Barcellos, Gabrielle B.; Ferreira-Paes, Taiana; Almeida-Amaral, Elmo E. (Frontiers in Chemistry, 2020)
Leishmaniasis is an infectious parasitic disease that is caused by protozoa of the genus Leishmania, a member of the Trypanosomatidae family. Leishmaniasis is classified by the World Health Organization as a neglected tropical disease that is responsible for millions of deaths worldwide. Although there are many possible treatments for leishmaniasis, these treatments remain mostly ineffective, expensive and long treatment, as well as causing side effects and leading to the development of resistance. For novel and effective treatments to combat leishmaniasis, many research groups have sought to utilize natural products. In addition to exhibiting potential as therapeutic compounds, natural products may also contribute to the development of new drugs based on their chemical structures. This review presents the most promising natural products, including crude extracts and isolated compounds, employed against Leishmania spp.